Effectiveness of insecticides against the adult stage of western corn beetle (Diabrotica virgifera virgifera LeConte, 1868) - Saliienko, V.; Fedorenko, V. (Quarantine and plant protection, 2023)
Goal. Assessment of chemical insecticides for WCR (Diabrotica virgifera virgifera LeConte, 1868) adults control for using in integrated corn pest management systems. Methods. Fields method. Trials conducted in 2021—2022 in farms in Bilyi Rukav Vinnytsia region and Ivanivka Kyiv region where corn was sown for 4 years. Techniques approved by the EPPO (Mediterranean Plant Protection Organization) are counting using yellow sticky traps, direct counting on plants, counting dead beetles, others. Results. 1—3 DAAT, the most effective was Avaunt EC (indoxacarb 150 g/l) at the rates of 0.17 l/ ha and 0.25 l/ ha with % reduction in population compared to the control 65.69 and 62.84, respectively, Karate Zeon SC (lambda-cyhalotryn 50 g/l) 0.3 l/ ha with 54.26% and Engio SC (thiamethoxam 141 g/l, lambda-cyhalotryn 50 g/l) 0.18 l/ ha — 48.54%. 12—14 DAAT, Avaunt EC insecticide at the rate of 0.17 l/ ha with 57.14% and Engio SC with 47.62% showed the highest percentage of population reduction, respectively. The records conducted during 2021—2022 were not fully statistically reliable. In 2021, the indicators of the calculations carried out using the technique of «direct counting on plants» were statistically reliable, in 2022 — counting using yellow sticky trap. When comparing the number of pests caught in yellow and blue sticky traps, the number in yellow traps was many times greater than in blue. Conclusions. Avaunt EC and Engio SC insecticides showed the most effective efficiency — 65.69% and 54.26%, the lower efficacy — Coragen SC with 11.38%. The highest efficiency can be observed 1—3 days after application, which is due to the direct contact of pests with CPP. 12—14 days after application, most of CPP showed a slight decrease in the number of pests, except Avaunt EC and Engio SC with 57.14 and 47.62%, respectively.